(untitled) (Journal of Dhaka National Medical College & Hospital, 2020)
Introduction: Care giver burden are actually an expression of addressing the adverse consequences of the care provided to the mentally ill patients. Review of the previous studies reveals a higher rate of burden among the care giver as compared to the general population. Objective: To find out the burden of care giver of mentally ill patient attended NIMH of Dhaka and to the association of duration of mental disorder on the burden of care giver of mentally ill patient attended NIMH of Dhaka. Methods and materials: This cross sectional descriptive type study was conducted at the National Institute of mental health (NIMH), Sher-e-Bangla Nagar Hospital of Dhaka in Bangladesh. The period of study was from July 2015 to June 20016. A total 300 respondent were included care givers of mentally ill patients. After pre tested written questionnaires and face to face interview and care giver burden measure by using ZBI (Zarit burden interview scale) for subjective burden and Montagomery Borgatta care giver burden scale for objective burden. Result: Majority 185(61.67%) of caregiver duration of care 0-10 years followed by 76(25.33%) of them 11-20 years and 39(13%) of them 21-30 years. More than three fourth (77.3%) of caregiver were moderate and 22.7% were mild objective burden. Almost two third (66%) of care giver were moderate subjective burden and rest(34%) were mild subjective burden (p<0.05). Conclusion: Study shows caregivers burden depends on the disease duration as well as some socio demographic factors. To provide a total care to the patients with mental disorders it is necessary to mitigate the caregiver’s burden. For this reason clinicians need to review periodically the status of caregiver’s burden. Further exploration is needed in future to assess the caregiver burden in community based, multi centered approach in long term follow up with a large sample size. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 28-32